Capital Inflows, Financial Development, and Domestic Investment : Determinants and Inter-Relationships - Spatafora, Nikola (IMF Working Papers; Working Paper ;, 2012)
We examine determinants of, and interactions between, capital inflows, financial development, and domestic investment in developing countries during 2001-07, a period of surging global liquidity and low interest rates. Reductions in the global price of risk and in domestic borrowing costs were the main contributors to the increase over time in net capital inflows and domestic credit. However, the large cross-country differences in domestic and international finance are best explained by fundamentals such as institutional quality, access to international export markets, and an appropriate macroeconomic policy. Both private capital inflows and domestic credit exert a positive effect on investment; they also mediate most of the investment impact of the global price of risk and domestic borrowing costs. Surprisingly, neither greater domestic credit nor greater institutional quality increase the extent to which capital inflows translate into domestic investment.